2016
DOI: 10.1515/ama-2016-0048
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Wear Resistance of the Composite with Microhybrid Structure and Nanocomposite

Abstract: The aim of the study was to compare microhardness and wear resistance of ceramic-polymer composites with micro and nano-hybrid structure. For the studies commercial composites were used, containing filler particles of the same type but different sizes, nano-sized (Filtek Ultimate) and micro-sized (Filtek Z250) composites. Tribological testing was conducted using ball-on-disc micro-tribometer. Vickers testing method was applied for microhardness studies with the use of Futertech FM 700 device. It has been demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The hardness of Bi 2 O 3 on the Mohs scale is 4–5 [46], while the hardness for PI on the Mohs scale is only 1 [47]. In [48, 49], it was shown that the introduction of inorganic particles significantly increases the microhardness of polymer composites.…”
Section: Resultsmentioning
confidence: 99%
“…The hardness of Bi 2 O 3 on the Mohs scale is 4–5 [46], while the hardness for PI on the Mohs scale is only 1 [47]. In [48, 49], it was shown that the introduction of inorganic particles significantly increases the microhardness of polymer composites.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the particle size, fillers can be divided into two main groups: macro filters (particles with dimensions from 0.2 to 70 µm) and nanofillers (particles with dimensions from 0.005 to 0.04 µm). This research aims to show the influence of a hybrid nanofiller's share on the composite's selected mechanical properties [15,16].…”
Section: Methodsmentioning
confidence: 99%
“…In this way, 25 samples (5 samples for each material) were made in the form of a cylinder with a height of 10 mm and a diameter of 8 mm (Figure 2). ence of a hybrid nanofiller's share on the composite's selected mechanical properties [15,16].…”
Section: Methodsmentioning
confidence: 99%
“…In previous works [1,61,62], it was proved that the wear of RBCs depends on the content of the filler in the matrix and its size. Generally, it can be assumed that the participation of nanoparticles in the structure of a surface layer causes strengthening and homogeneity as well as slowing down the wear process [34,63]. In addition, nanofiller particles can have a positive effect on load transfer from the matrix to the filler [19].…”
Section: Sliding Wearmentioning
confidence: 99%